2016
DOI: 10.1210/jc.2016-1076
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Famine in Early Life and Nonalcoholic Fatty Liver Disease in Adulthood

Abstract: Exposure to the Great Famine in early life had sex-specific association with moderate-severe NAFLD. This indicates that malnutrition in early life may influence the development of adult NAFLD; thus pregnant women and their infants and children may require the highest priority in obtaining nutritional relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 35 publications
11
83
1
Order By: Relevance
“…Our data (n = 6899) were from the SPECT-China study 54, 55 . The sampling method was described in detail in our previous study 23 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data (n = 6899) were from the SPECT-China study 54, 55 . The sampling method was described in detail in our previous study 23 .…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaires about demographic characteristics, medical history and lifestyle risk factors and anthropometric data were constructed by the same trained staff as previously described 54, 55 . Body weight, height and the calculation of BMI were calculated consistently with the previous study 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same cohort, prenatal exposure to famine was associated with a more atherogenic lipid profile than those who were not exposed to famine in utero 18 . Early-life exposure to famine during the Great Chinese Famine (1958–1961) was associated with a sex-specific increase in the prevalence of moderate–severe NAFLD in adulthood, providing direct evidence of the link between poor fetal nutrition and perturbed liver function 19 .…”
Section: Liver Physiologymentioning
confidence: 99%
“…The emerging pandemic was partially caused by population growth, rapidly aging and changes of diet and lifestyle [2, 3, 5]. However, recent studies indicated that the early life famine exposure also might increase the later susceptibility to some common chronic diseases [6], including metabolic syndrome [7], diabetes [8], and fatty liver disease [9]. …”
Section: Introductionmentioning
confidence: 99%